Genetic characterization of indigenous rhizobia strains from the coastal tableland efficient for the pigeonpea and cowpea crops - Fernandes, Marcelo Ferreira; Fernandes, Roberta Pereira Miranda; Hungria, Mariangela (Pesquisa Agropecuaria Brasileira, 2003)
The objective of this work was to characterize genetically seven indigenous rhizobial strains from the coastal tableland of Sergipe, Brazil, with high efficiency of biological nitrogen fixation with the pigeonpea (Cajanus cajan) and cowpea (Vigna unguiculata) crops. The DNA amplification with the PCR (polymerase chain reaction) technique and the specific primer BOX indicated a high level of genetic diversity, with all isolates showing unique profiles of DNA. The BOX-PCR analysis also indicated that this method is efficient to characterize strains but not to define rhizobial species. The RFLP (restriction fragment length polymorphism) analysis of the 16S rRNA region and of the intergenic region between the 16S and the 23S rRNA genes with five restriction enzymes, as well as the partial sequencing of the 16S rRNA region allowed the classification of the strains into the genera Bradyrhizobium and Rhizobium. There was an agreement between the results obtained by the analysis of the 16S rRNA region, but one strain differed when the intergenic space was considered. The results obtained with strain R11 showed a high level of genetic diversity when compared to the described rhizobial species, including differences in several bases of the 16S rRNA region, and might indicate a new species.